Influence of vermicompost and vermiwash on physico chemical properties of rice cultivated soil - K., Suresh Kumar R, Anandan A., Tharmaraj K, Ganesh P.; Kolanjinathan (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In this study the effect of vermicompost on soil chemical and physical properties was evaluated during samba rice cultivation studies. The experiments were arranged in a completely randomized block design manner with three replications. The soil sampling and plant growth measurements were carried out for two months, ie., during initial and final stages. The present study has been carried out to study the impact of various vermiproduct such as vemicompost, vermiwash and mixture of vermicompost and vermiwash on soil physico-chemical properties during the pot culture studies of samba rice. The physical properties such as the pH, electrical conductivity (EC), porosity, moisture content, water holding capacity and chemical properties like nitrogen, phosphorous, potassium, calcium and magnesium were found distinctly enhanced in vermicompost treated soil, where as the corresponding physico-chemical values in control were minimum. The soil treated with vermicompost had significantly more electrical conductivity in comparison to unamended pots. The addition of vermicompost in soil resulted in decrease of soil pH. The physical properties such as water holding capacity, moisture content and porosity in soil amended with vermicompost were improved.Ã‚Â The vermiproduct treated plants exhibit faster and higher growth rate and productivity than the control plants.Ã‚Â Among the treated group, the growth rate was high in the mixture of vermicompost and vermiwash treated plants, than the vermicompost and vermiwash un-treated plants. The maximum range of some plant parameter’s like number of leaves, leaf length, height of the plants and root length of plant, were recorded in the mixture of vermicompost and vermiwash. The results of this experiment revealed that addition of vemicompost had significant positive effects on the soil physical, chemical properties and plant growth parameters.